Synthesis and Characterization of (Five, Six) Hetrocycyclic Derivatives from Imidazole and Studying of their Biological Activity - Lina Saadi (Journal of Global Pharma Technology, 2018)
This research involve synthesis (Pyrazol,isoxazole ,Oxazine, Thiazine, Pyridine, pyrimidine) derivatives by three different steps, The first step includes coupling reaction between 3-amino acetophenonediazonium chloride with imidazole in alkaline alcoholic solution to form (1-(3-((1H-imidazol-2-yl)diazenyl)phenyl)ethan-1-one) (1) ,while second step includes reaction(1) with (3,4-Dimethoxy benzaldehyde) to get chalcone derivative (2),while the third step includes reaction(2) with (hydrazine ,phenyl hydrazine ,2,4 dinitrophenyl hydrazine, hydroxylamine hydrochlorid, urea, tiourea, ethyl cyanoacetate, malononitrile, guanidine hydrochloride) to get (five and six ) hetrocyclicderivatives, heterocyclic compounds have been characterized by FT-IR, 1H-NMR and13C-NMR  analysis and study the biological activity for all derivatives to word two types of becteria.Keywords:  Azo, pyrazole, chalcone ,oxazine, thiazine,  pyridine, pyrimidine.